ILOKUSI DIREKTIF DALAM REKAMAN SUARA TERSANGKA PELECEHAN SEKSUAL I WAYAN AGUS SUARTAMA - Nafysah, Durrotun; Pujihastuti, Etin; Ulfa Martha, Nia (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2026)
Language is not merely a tool for communication but also an instrument of power that reflects domination and social control between the speaker and the listener. In the context of sexual harassment, speech acts often serve as manipulative tools to influence, persuade, or control victims without physical violence. This study aims to describe the types and functions of directive illocutionary acts found in the audio recordings and public statements of I Wayan Agus Suartama, a suspect in a sexual harassment case. This research employed a descriptive qualitative method with a pragmatic approach. The data consisted of the suspect’s utterances, which were analyzed based on Searle’s (1979) speech act theory and classified into directive categories such as requests, commands, prohibitions, and advice. The findings reveal that the directive speech acts used by Agus are generally indirect and persuasive, expressed through declarative forms that conceal their true intentions. These utterances function to build trust, manipulate the victim’s emotions, and construct a positive public image. Thus, directive illocutionary acts in this case serve not only as linguistic instructions but also as instruments of power and psychological manipulation, illustrating the interplay between language and power within the discourse of sexual harassment.